Patient safety culture in three inpatient services of a public hospital in Peru - Suarez Baldeon, Veronica Mercedes (2024)
Objective. To analyze the patient safety culture in three inpatient services of a public hospital in Peru. Methods. A descriptive and cross-sectional study with a quantitative approach was conducted among healthcare professionals in the gynecology-obstetrics, surgery, and internal medicine inpatient services at the Hospital de Lima Este Vitarte. The sample consisted of 93 healthcare professionals, who were administered the SOPS 2.0 questionnaire. Frequencies and percentages were estimated. The Kruskal-Wallis and Mann-Whitney U tests were used to analyze the significance of the dimensions among the three services. Results. In gynecology obstetrics, 57.6% evaluated the safety culture as good to excellent, compared to 87.1% in internal medicine and 72.4% in surgery. Regarding adverse events, 60.6% in gynecology-obstetrics reported none, compared to 19.4% in internal medicine and 51% in surgery. Key dimensions with signifcant differences included teamwork (p = 0.000), response to errors (p = 0.001), and supervisor support (p = 0.000). The main strength was teamwork (75% in internal medicine), while opportunities for improvement included organizational learning and communication about errors in gynecology-obstetrics, and work pressure and pace in internal medicine and surgery. Significant differences in patient safety culture were found among the three services (p < 0.05). Conclusions. The patient safety culture varies signifcantly among the analyzed inpatient services. Differences in key areas highlight the need to implement specifc strategies to strengthen safety culture in each service, thereby ensuring safer and more effective care at Hospital de Lima Este Vitarte.